THU0455 PHARMACOKINETICS (PK) OF A SINGLE INTRA-ARTICULAR (IA) INJECTION OF CNTX-4975 (TRANS-CAPSAICIN) VS TOPICAL 8% CAPSAICIN PATCH. (June 2019) - Stevens, Randall; Guedes, Kimberly; Armas, Eddie; Smith, Valerie; Volosov, Andrew
Abstract : Background: CNTX-4975 is in phase 3 trials for treatment of moderate to severe pain associated with knee osteoarthritis (OA). PK data from prior studies of CNTX-4975 in subjects with moderate to severe knee OA pain suggest low systemic and short-term exposure, similar to the FDA-approved topical capsaicin 8% patch. Objectives: We compared single-dose systemic exposure to trans - and cis -capsaicin following IA injection of CNTX-4975 (>99.5% trans -capsaicin, <0.5% total impurities) with 8% capsaicin patch in subjects with moderate to severe knee OA pain. Methods: This open-label, crossover study enrolled adults aged 50–75 y with moderate to severe knee OA pain in ≥1 knee (most painful knee, index knee; nonindex knee, no to mild pain [0–1; NPRS 0–4 scale]). Subjects were randomized 1:1 to 2 sequences: A (CNTX-4975 1 mg IA, index knee) followed by B (topical capsaicin 8% patch, posterior rib cage for 60 min) or BA sequence, with ≥7-day washout between treatments. Plasma samples for trans - and cis -capsaicin concentration assays were taken before and at specified times after study treatment. PK parameters, including maximum observed plasma concentration (Cmax ), area under the plasma concentration-time curve from time 0 to last quantifiable plasma concentration (AUC0-t ) and to infinity (AUC0-∞ ), time to Cmax (Tmax ), and half-life (t1/2 ), were determined. PK parameters were reported using descriptive statistics. Geometric means ratios of ln-transformed AUC0-t, AUC0-∞, and Cmax were evaluated using ANOVA. Results: Sixteen subjects (median age, 62 y; female, 62.5%) were randomized to treatment (PK analysis population). Tmax showed more rapid absorption of trans -capsaicin from IA CNTX-4975 vs the topical patch (Table ). AUC0-t and Cmax indicated greater trans -capsaicin exposure with CNTX-4975 vs the patch; however, exposure was short term, with mean t1/2 0.5 h. Cis -capsaicin concentrations were insufficient for calculating PK. Conclusion: Trans -capsaicin from CNTX-4975 injection was rapidly absorbed and eliminated. The extent of systemic exposure to trans -capsaicin was significantly higher after CNTX-4975 vs the 8% capsaicin patch. Disclosure of Interests: Randall Stevens Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, Kimberly Guedes Employee of: Centrexion Therapeutics Corp, Eddie Armas: None declared, Valerie Smith Consultant for: Premier Research, Andrew Volosov Consultant for: Premier Research